Anticancer compounds from in vitro cultures of rare medicinal plants - Ionkova, Iliana (Pharmacognosy Reviews)
Malignant diseases are the second mortality cause within the human population. Due to their complex structure with several chiral centres important anticancer agents are still extracted from plants and not synthesized chemically on a commercial scale. In the coming decades, several new enabling technologies will be required to develop the next generation of advanced plantbased pharmaceuticals. This review summarizes our results concerning the production of certain anticancer compounds from tissue cultures of rare medicinal Astragalus and Linum plants. The various problems involved and the possible ways to overcome using biotechnological approaches are discussed on the basis of examples from our own research.
Keywords: plant anticancer compounds; in vitro production; saponins; lignans; Astragalus; Linum